Gaya bahasa tasybih dalam Al-qur’an: Studi balaghah terhadap ayat-ayat kiasan - Hidayah, Khikmatul; Nuruddien, Muhammad (Maliki Interdisciplinary Journal, 2025)
This research aims to examine the stylistic structure of tasybih language in the Al-Qur’an through a balaghah science approach, especially in the realm of bayan science. Tasybih is a form of imagery that is widely used in the Qur’an as a medium for conveying divine messages that are profound, aesthetic, and touch the emotional and intellectual dimensions of humans. The approach used in this research is library research with descriptive qualitative methods. The main data source is verses from the Qur’an which contain tasybih elements, while secondary data sources come from scientific journals, articles and classical and contemporary references that discuss the theory of balaghah, especially parables. The research procedure includes identification, selection and classification of verses that contain elements of comparison, both explicit and implied. Each identified verse is then analyzed based on the tasybih components, namely: musyabbah (which is similar), musyabbah bih (which is a comparison), tasybih tools (comparison letters or words), and face of the syabah (similarity side). The results of the study show that tasybih in the Qur’an does not merely function as a rhetorical device, but also as a means of conveying the values ​​of monotheism, morality, and spirituality in depth. Although bayan science includes several other branches of discussion such as kinayah and majaz, tasybih has a distinctive feature in its structure and power of imagination. It forms a bridge between logical meaning and aesthetic imagery, thus enriching the reader’s understanding of the messages of the Qur’an. Therefore, understanding the style of tasybih language is very important in revealing the beauty of the language of the Qur’an comprehensively and contextually.